High-performance magnetic glass based on al2o3 and method for manufacturing the same

CN123003144APending Publication Date: 2026-10-30CNBM RESEARCH INSTITUTE FOR ADVANCED GLASS MATERIALS GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611152790.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

因为Al2O3作为玻璃组分可有效增加玻璃的玻璃化转变温度和析晶温度,有效地抑制磁性玻璃中Fe3O4晶核尺寸,从而影响磁性玻璃的性能

Benefits of technology

本发明通过引入氧化铝作为晶粒生长抑制剂,借助其对玻璃网络结构的增强作用以及对Fe3O4晶核迁移和晶界扩散的物理阻碍效应,能够有效抑制磁性晶粒的异常粗化,使析出晶粒尺寸得以在纳米尺度范围内实现连续可调,克服了现有技术中晶粒尺寸难以控制、分布宽化的技术难题;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003144A_ABST
    Figure CN123003144A_ABST
Patent Text Reader

Abstract

The application discloses high-performance magnetic glass based on Al2O3 and a preparation method thereof, and belongs to the technical field of functional glass materials. The basic components of the magnetic glass include P2O5, B2O3, Na2O, CeO2 and Fe2O3, and Al2O3 is introduced as a reinforcing control component in an additional manner. The preparation method is as follows: after the raw materials are uniformly mixed, the mixture is smelted at 1200-1400 DEG C, and then is subjected to forming and annealing treatment, so that the magnetic glass-ceramic is obtained. By controlling the introduction amount of Al2O3, the abnormal growth of Fe3O4 grains in the glass matrix is effectively inhibited, the controllable adjustment of the grain size in the nanometer scale range is realized, and it is ensured that Fe3O4 is the only precipitated magnetic crystal phase. The magnetic glass obtained by the application has excellent magnetic performance and mechanical performance, the saturation magnetization is significantly enhanced, the coercive force is obviously improved, the bending strength is greatly improved, and the synergy of functionality and structural stability is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional glass materials technology, specifically relating to a high-performance magnetic glass based on Al2O3 and its preparation method. Background Technology

[0002] Magnetic glass (also known as magneto-optical glass or microcrystalline glass) is a type of composite material formed by uniformly dispersing magnetic nanocrystals (such as Fe3O4, γ-Fe2O3, etc.) in an amorphous glass matrix. It combines the responsive characteristics of magnetic materials with the electrical insulation, chemical stability, and easy molding properties of glass materials. It has broad application prospects in magneto-optical devices, high-frequency magnetic cores, electromagnetic shielding, and biothermal therapy.

[0003] Currently, the commonly used method for preparing magnetic glass is the melt-crystallization method, which involves adding iron oxides to the base glass composition, melting it at high temperature, rapidly cooling it, and then subjecting it to appropriate heat treatment to precipitate the magnetic crystalline phase from the glass matrix. However, existing technologies still have shortcomings, severely restricting the improvement of material performance and industrialization. First, the size of the precipitated magnetic grains is difficult to control, easily growing to the micrometer scale (typically >800nm), leading to a weakening of the superparamagnetic effect, a decrease in coercivity, and a broadening of the grain size distribution, affecting the consistency of magnetic properties. Second, due to the introduction of a large amount of iron oxides, the strength of the glass network structure decreases, resulting in greater brittleness and reduced bending strength, limiting its application in structural-functional integrated components. Third, during the high-temperature melting process, Fe... 2+ / Fe 3+ The ratio is difficult to control stably, and it is easy to generate non-target crystalline phases such as α-Fe2O3, which reduces the saturation magnetization.

[0004] To address the aforementioned issues, existing research has shown that adding a small amount of alumina (Al2O3) can improve the chemical stability and mechanical strength of glass. This is because Al2O3, as a glass component, can effectively increase the glass transition temperature and crystallization temperature, effectively suppressing the size of Fe3O4 crystal nuclei in magnetic glasses, thus affecting their performance. However, current reports mostly focus on the improvement of glass thermal stability or chemical durability by Al2O3, while systematic research on the nanoscale control of Fe3O4 grain size by Al2O3 content, its influence on the selective precipitation of a single crystalline phase, and its synergistic enhancement effect on saturation magnetization and flexural strength remains lacking. Therefore, developing a magnetic glass capable of simultaneously achieving nanoscale grain size, a single Fe3O4 crystalline phase, and improved saturation magnetization and flexural strength, along with its preparation method, has significant technological value and industrialization implications. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a high-performance magnetic glass based on Al2O3 and its preparation method.

[0006] The objective of this invention can be achieved through the following technical solutions: A high-performance magnetic glass based on Al2O3, comprising a base glass component and additional components.

[0007] As a further technical solution, the basic glass component is composed of the following oxides by weight percentage: phosphorus pentoxide (P2O5): 35-44 wt%, boron trioxide (B2O3): 17-23 wt%, sodium oxide (Na2O): 8-11 wt%, cerium oxide (CeO2): 0.5-1.2 wt%, ferric oxide (Fe2O3): 27-33 wt%; preferably: phosphorus pentoxide: 40 wt%, boron trioxide: 20 wt%, sodium oxide: 9 wt%, cerium oxide: 1 wt%, ferric oxide: 30 wt%.

[0008] As a further technical solution, the added component is alumina, and the amount used is 2-10 wt% of the total weight of the base glass component.

[0009] This invention can effectively suppress the size of magnetic crystallites and improve the saturation magnetization, coercivity and bending strength of magnetic glass by controlling the Al2O3 content.

[0010] This invention also provides a method for preparing high-performance magnetic glass based on Al2O3, comprising the following steps: A1. Weigh out the raw materials of phosphorus pentoxide, boron trioxide, and sodium oxide according to the weight percentage, add them to a ball mill jar with aluminum oxide, cerium oxide, and ferric oxide, and ball mill and mix them evenly. After drying, the compound material is obtained. A2. Place the batch material into a crucible and then place it in a high-temperature muffle furnace for melting to form a homogeneous glass melt; A3. Quickly pour the molten glass into a preheated mold (copper or stainless steel) and let it cool and solidify to obtain a glass block; A4. The glass block is quickly transferred into an annealing furnace, kept at a constant temperature for annealing, and then cooled to room temperature to eliminate internal stress, thereby obtaining high-performance magnetic glass based on Al2O3.

[0011] As a further technical solution, the raw materials for phosphorus pentoxide, boron trioxide, and sodium oxide are, in order, ammonium dihydrogen phosphate, boric acid, and sodium carbonate.

[0012] As a further technical solution, in the ball milling process, the mass ratio of raw materials, zirconium oxide balls and ethanol solvent is 1:1:2, and the ball milling time is 1-3 hours.

[0013] As a further technical solution, the drying temperature is 80-100℃ and the time is 3-4 hours.

[0014] As a further technical solution, the melting process adopts a stepped heating method, first heating from room temperature to 1100℃ at 5℃ / min and holding for 1 hour, and then heating from 1100℃ to 1200-1400℃ at 3℃ / min and holding for 1-4 hours.

[0015] As a further technical solution, the temperature of the preheating mold is 400-500℃.

[0016] As a further technical solution, the temperature of the annealing furnace is 400℃ and the annealing time is 1-3h.

[0017] The beneficial effects of this invention are: This invention introduces alumina as a grain growth inhibitor. By leveraging its enhancement effect on the glass network structure and its physical barrier effect on Fe3O4 crystal nucleus migration and grain boundary diffusion, it can effectively suppress the abnormal coarsening of magnetic grains, enabling the precipitated grain size to be continuously tunable within the nanoscale range. This overcomes the technical difficulties of controlling grain size and widening distribution in the prior art. This invention, through reasonable component design and precise heat treatment, ensures that only the Fe3O4 magnetic crystalline phase precipitates in the glass matrix, effectively avoiding the formation of α-Fe2O3, FeO or other complex ferrite impurities, guaranteeing the purity of the magnetic functional phase, and eliminating the dilution effect of non-target crystalline phases on magnetic properties. The introduction of alumina has a dual effect: on the one hand, it increases the proportion of nanoscale magnetic domains by refining the grain size, thereby enhancing the saturation magnetization and coercivity; on the other hand, it improves the interatomic bonding force by enhancing the connectivity of the glass network structure. At the same time, the uniformly dispersed nanocrystals have a deflection and bridging effect on crack propagation, significantly improving the bending strength. This breaks through the technical bottleneck of "difficulty in achieving both magnetic and mechanical properties" in the field of magnetic glass, and achieves the unity of functional characteristics and structural stability. This invention does not require complex atmosphere control equipment (such as reducing or inert gas protection) and can complete melting in ordinary air atmosphere; it has a wide melting temperature range, a large holding time window, a simple and easy annealing process, low equipment requirements, and a wide operating window, which helps to reduce production costs and has good prospects for industrialization and application. Attached Figure Description

[0018] The invention will now be further described with reference to the accompanying drawings.

[0019] Figure 1 The XRD patterns are of the magnetic glasses prepared in Examples 1-5 of this invention. Figure 2 SEM images of the magnetic glasses prepared in Examples 1-5 of this invention; Figure 3The diagram shows the bending strength of the magnetic glass prepared in Examples 1-5. Detailed Implementation

[0020] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0021] Example 1

[0022] A method for preparing high-performance magnetic glass based on Al2O3 includes the following steps: A1. The base glass components are as follows by weight percentage: phosphorus pentoxide: 40wt%, boron trioxide: 20wt%, sodium oxide: 9wt%, cerium oxide: 1wt%, ferric oxide: 30wt%; with added alumina: 2wt%. Weigh the following raw materials: ammonium dihydrogen phosphate, boric acid, sodium carbonate, alumina, cerium oxide, and ferric oxide. Add them to a ball mill jar and ball mill for 1 hour (the mass ratio of total raw materials, zirconium oxide balls, and ethanol solvent is 1:1:2). Dry at 80℃ for 3 hours to obtain the batch material. A2. Place the batch material into a crucible and then place it in a high-temperature muffle furnace. First, heat the material from room temperature to 1100℃ at a rate of 5℃ / min and hold for 1 hour. Then, heat the material from 1100℃ to 1200℃ at a rate of 3℃ / min and hold for 1 hour to melt the raw material into a homogeneous glass melt. A3. Quickly pour the molten glass into a preheated copper mold at 500°C and let it cool and solidify to obtain a glass block; A4. The glass block is quickly transferred into an annealing furnace at 400℃ and annealed for 1 hour. Then it is cooled to room temperature at a rate of 5℃ / min to eliminate internal stress and obtain high-performance magnetic glass based on Al2O3.

[0023] Example 2

[0024] A method for preparing high-performance magnetic glass based on Al2O3 includes the following steps: A1. The base glass components are as follows by weight percentage: phosphorus pentoxide: 40wt%, boron trioxide: 20wt%, sodium oxide: 9wt%, cerium oxide: 1wt%, ferric oxide: 30wt%; with added alumina: 4wt%. Weigh the following raw materials: ammonium dihydrogen phosphate, boric acid, sodium carbonate, alumina, cerium oxide, and ferric oxide. Add them to a ball mill jar and ball mill for 1 hour (the mass ratio of total raw materials, zirconium oxide balls, and ethanol solvent is 1:1:2). Dry at 90°C for 4 hours to obtain the batch material. A2. Place the batch material into a crucible and then place it in a high-temperature muffle furnace. First, heat the material from room temperature to 1100℃ at a rate of 5℃ / min and hold for 1 hour. Then, heat the material from 1100℃ to 1200℃ at a rate of 3℃ / min and hold for 1 hour to melt the raw material into a homogeneous glass melt. A3. Quickly pour the molten glass into a preheated copper mold at 500°C and let it cool and solidify to obtain a glass block; A4. The glass block is quickly transferred into an annealing furnace at 400℃ and annealed for 1 hour. Then it is cooled to room temperature at a rate of 5℃ / min to eliminate internal stress and obtain high-performance magnetic glass based on Al2O3.

[0025] Example 3

[0026] A method for preparing high-performance magnetic glass based on Al2O3 includes the following steps: A1. The base glass components are as follows by weight percentage: phosphorus pentoxide: 40wt%, boron trioxide: 20wt%, sodium oxide: 9wt%, cerium oxide: 1wt%, ferric oxide: 30wt%; with added alumina: 6wt%. Weigh the following raw materials: ammonium dihydrogen phosphate, boric acid, sodium carbonate, alumina, cerium oxide, and ferric oxide. Add them to a ball mill jar and ball mill for 3 hours (the mass ratio of total raw materials, zirconium oxide balls, and ethanol solvent is 1:1:2). Dry at 100℃ for 4 hours to obtain the batch material. A2. Place the batch material into a crucible and then place it in a high-temperature muffle furnace. First, heat the material from room temperature to 1100℃ at a rate of 5℃ / min and hold for 1 hour. Then, heat the material from 1100℃ to 1200℃ at a rate of 3℃ / min and hold for 1 hour to melt the raw material into a homogeneous glass melt. A3. Quickly pour the molten glass into a preheated copper mold at 500°C and let it cool and solidify to obtain a glass block; A4. The glass block is quickly transferred into an annealing furnace at 400℃ and annealed for 1 hour. Then it is cooled to room temperature at a rate of 5℃ / min to eliminate internal stress and obtain high-performance magnetic glass based on Al2O3.

[0027] Example 4

[0028] A method for preparing high-performance magnetic glass based on Al2O3 includes the following steps: A1. The base glass components are as follows by weight percentage: phosphorus pentoxide: 40wt%, boron trioxide: 20wt%, sodium oxide: 9wt%, cerium oxide: 1wt%, ferric oxide: 30wt%; with added alumina: 8wt%. Weigh the following raw materials: ammonium dihydrogen phosphate, boric acid, sodium carbonate, alumina, cerium oxide, and ferric oxide. Add them to a ball mill jar and ball mill for 1 hour (the mass ratio of total raw materials, zirconium oxide balls, and ethanol solvent is 1:1:2). Dry at 100℃ for 4 hours to obtain the batch material. A2. Place the batch material into a crucible and then place it in a high-temperature muffle furnace. First, heat the material from room temperature to 1100℃ at a rate of 5℃ / min and hold for 1 hour. Then, heat the material from 1100℃ to 1200℃ at a rate of 3℃ / min and hold for 1 hour to melt the raw material into a homogeneous glass melt. A3. Quickly pour the molten glass into a preheated copper mold at 500°C and let it cool and solidify to obtain a glass block; A4. The glass block is quickly transferred into an annealing furnace at 400℃ and annealed for 1 hour. Then it is cooled to room temperature at a rate of 2℃ / min to eliminate internal stress and obtain high-performance magnetic glass based on Al2O3.

[0029] Example 5

[0030] A method for preparing high-performance magnetic glass based on Al2O3 includes the following steps: A1. The base glass components are as follows by weight percentage: phosphorus pentoxide: 40wt%, boron trioxide: 20wt%, sodium oxide: 9wt%, cerium oxide: 1wt%, ferric oxide: 30wt%; with added alumina: 10wt%. The following raw materials—ammonium dihydrogen phosphate, boric acid, sodium carbonate, alumina, cerium oxide, and ferric oxide—are weighed and added to a ball mill jar for ball milling and mixing for 1 hour (the mass ratio of total raw materials, zirconium oxide balls, and ethanol solvent is 1:1:2). The mixture is then dried at 100°C for 4 hours to obtain the batch material. A2. Place the batch material into a crucible and then place it in a high-temperature muffle furnace. First, heat the material from room temperature to 1100℃ at a rate of 5℃ / min and hold for 1 hour. Then, heat the material from 1100℃ to 1200℃ at a rate of 3℃ / min and hold for 1 hour to melt the raw material into a homogeneous glass melt. A3. Quickly pour the molten glass into a preheated copper mold at 500°C and let it cool and solidify to obtain a glass block; A4. The glass block is quickly transferred into an annealing furnace at 400℃ and annealed for 1 hour. Then it is cooled to room temperature at a rate of 5℃ / min to eliminate internal stress and obtain high-performance magnetic glass based on Al2O3.

[0031] X-ray diffractometer was used to test Examples 1-5, and the results are as follows: Figure 1 As shown; The results of tests conducted using a scanning electron microscope on Examples 1-5 are as follows: Figure 2 As shown; The magnetic glass samples from Examples 1-5 were cut into strips measuring 25mm × 4mm × 3mm. The tensile surfaces of the samples were chamfered and polished to a surface roughness Ra ≤ 0.8μm. The three-point bending method was used on a universal testing machine with a span of 20mm and a loading rate of 0.5mm / min. The bending strength was determined and calculated, and the results are as follows: Figure 3 As shown.

[0032] The properties of the magnetic glasses prepared in Examples 1-5 were measured, and the results are shown in Table 1. Table 1

[0033] from Figure 1 It can be seen that the precipitated crystalline phase of this invention is only Fe3O4, with no impurities. Figure 2 It can be seen that the crystals of the present invention are spherical, and the grain size of Examples 1-5 is significantly smaller, the number of crystals increases, and the crystal size decreases from 800nm ​​to 200nm; from Figure 3 It can be seen that the introduction of Al2O3 in Examples 1-5 of the present invention enhances the connectivity of the glass network structure and improves the interatomic bonding force. Furthermore, as the Al2O3 content increases from 2wt% to 10wt%, the bending strength shows a significant upward trend (from 12MPa to 30MPa). As shown in Table 1, in Examples 1-5 of the present invention, the increase of Al2O3 can enhance the saturation magnetization and coercivity, which has important application value for the functionalization of magnetic glass.

[0034] In summary, this invention, by introducing an appropriate amount of Al2O3 into a phosphate glass system and matching it with optimized melting and annealing processes, achieves nanoscale size control and single-phase precipitation of Fe3O4 magnetic grains, simultaneously improving the material's magnetic properties and flexural strength. This effectively overcomes the technical challenges of coarse grains, impure crystalline phases, and the difficulty in synergistically enhancing mechanical and magnetic properties in existing technologies. Furthermore, this preparation method has a wide operating window and does not require complex atmosphere control, demonstrating promising prospects for industrial application.

[0035] In the description of this specification, the references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0036] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.

Claims

1. A high-performance magnetic glass based on Al2O3, comprising a base glass component and additional components, characterized in that, The base glass component is composed of the following oxides by weight percentage: phosphorus pentoxide: 35-44 wt%, boron trioxide: 17-23 wt%, sodium oxide: 8-11 wt%, cerium oxide: 0.5-1.2 wt%, ferric oxide: 27-33 wt%; the added component is aluminum oxide, and the amount used is 2-10 wt% of the total weight of the base glass component.

2. A method for preparing a high-performance magnetic glass based on Al2O3, used to prepare the high-performance magnetic glass based on Al2O3 as described in claim 1, characterized in that, Includes the following steps: A1. Weigh out the raw materials of phosphorus pentoxide, boron trioxide, and sodium oxide according to the weight percentage, add them to a ball mill jar with aluminum oxide, cerium oxide, and ferric oxide, and ball mill and mix them evenly. After drying, the compound material is obtained. A2. Place the batch material into a crucible and then place it in a muffle furnace for melting to form a homogeneous glass melt; A3. Quickly pour the molten glass into a preheated mold and let it cool and solidify to obtain a glass block; A4. The glass block is quickly transferred into an annealing furnace, kept at a constant temperature for annealing, and then cooled to room temperature to obtain a high-performance magnetic glass based on Al2O3.

3. The method for preparing high-performance magnetic glass based on Al2O3 according to claim 2, characterized in that, The raw materials for phosphorus pentoxide, boron trioxide, and sodium oxide are, in order, ammonium dihydrogen phosphate, boric acid, and sodium carbonate.

4. The method for preparing high-performance magnetic glass based on Al2O3 according to claim 2, characterized in that, The drying temperature is 80-100℃, and the time is 3-4 hours.

5. The method for preparing high-performance magnetic glass based on Al2O3 according to claim 2, characterized in that, The melting process adopts a stepped heating method, first heating from room temperature to 1100℃ at 5℃ / min and holding for 1 hour, then heating from 1100℃ to 1200-1400℃ at 3℃ / min and holding for 1-4 hours.

6. The method for preparing high-performance magnetic glass based on Al2O3 according to claim 2, characterized in that, The temperature of the preheated mold is 400-500℃.

7. The method for preparing high-performance magnetic glass based on Al2O3 according to claim 2, characterized in that, The annealing furnace is set at 400°C and the annealing time is 1-3 hours.